Development of a Physics Laboratory Activity Kit for the Do-It-Yourself (DIY) Physics Equipment and Laboratory Activity - Malicoban, Elesar V.; Castro, Ellen J. (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
The main objective of this study was to develop a Physics laboratory activity kit for the Do-It-Yourself (DIY) Physics equipment and laboratory activity to be used in Physics classes of high school students. The resulting kit was assessed by the selected pre-service and in-service Physics teachers. This study employed a mixed methods. Assessment of the laboratory activity kit which includes the Student Worksheets, Teacher’s Guide, and Equipment Construction was done by the in-service and pre-service Physics teachers in order to ensure a workable DIY Physics equipment and quality laboratory activity kit which shall be of great use in Physics class. The pre-service and in-service rated the Student Worksheet as very good. The DIY Physics equipment was workable. The laboratory activity for the DIY Physics equipment was appropriate for the fourth-year students. The Teacher’s Guide in the laboratory activity kit was very good and can guide the teacher on what to do before, during, and after the activity. The Equipment Construction was very good and appropriate for the teacher’s guide and laboratory activity.